World Migration Report 2020 - International Organization for Migration (United Nations, 2019)
Since 2000, IOM has been producing world migration reports. The World Migration Report 2020, the tenth in the world migration report series, has been produced to contribute to increased understanding of migration throughout the world. This new edition presents key data and information on migration as well as thematic chapters on highly topical migration issues, and is structured to focus on two key contributions for readers: Part I: key information on migration and migrants (including migration-related statistics); and Part II: balanced, evidence-based analysis of complex and emerging migration issues.